The Effect of Early Treatment with Intravenous Magnesium Sulfate on the Incidence of Cardiac Comorbidities in Hospitalized Stroke Patients - Kameron Bechler; Kristina Shkirkova; Jeffrey L. Saver; Sidney Starkman; Scott Hamilton; David S. Liebeskind; Marc Eckstein; Samuel Stratton; Frank Pratt; Robin Conwit; Nerses Sanossian (Hindawi-Wiley, 2020)
Background. Cardiac adverse events are common among patients presenting with acute stroke and contribute to overall morbidity and mortality. Prophylactic measures for the reduction of cardiac adverse events in hospitalized stroke patients have not been well understood. We sought to investigate the effect of early initiation of high-dose intravenous magnesium sulfate on cardiac adverse events in stroke patients. Methods. This is a secondary analysis of the prehospital Field Administration of Stroke Therapy-Magnesium (FAST-MAG) randomized phase-3 clinical trial, conducted from 2005-2013. Consecutive patients with suspected acute stroke and a serum magnesium level within 72 hours of enrollment were selected. Twenty grams of magnesium sulfate or placebo was administered in the ambulance starting with a 15-minute loading dose intravenous infusion followed by a 24-hour maintenance infusion in the hospital. Results. Among 1126 patients included in the analysis of this study, 809 (71.8%) patients had ischemic stroke, 277 (24.6%) had hemorrhagic stroke, and 39 (3.5%) with stroke mimics. The mean age was 69.5 (SD13.4) and 42% were female. 565 (50.2%) received magnesium treatment, and 561 (49.8%) received placebo. 254 (22.6%) patients achieved the target, and 872 (77.4%) did not achieve the target, regardless of their treatment group. Among 1126 patients, 159 (14.1%) had at least one CAE. Treatment with magnesium was not associated with fewer cardiac adverse events. A multivariate binary logistic regression for predictors of CAEs showed a positive association of older age and frequency of CAEs (R=1.04, 95% CI 1.03-1.06, p<0.0001). Measures of early and 90-day outcomes did not differ significantly between the magnesium and placebo groups among patients who had CAEs. Conclusion. Treatment of acute stroke patients with magnesium did not result in a reduction in the number or severity of cardiac serious adverse events.